Проблеми і перспективи розвитку інформаційних технологій в сільському господарстві - Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianska, Natalia; Маніта, Ігор Юрійович; Манита, Игорь Юрьевич; Manita, Ihor; Подашевська, О. (My University, 2020)
UK: Застосування інформаційно-комунікаційних технологій - гармонійний шлях виходу з замкнутих технологій, які характеризуються сильною поляризацією і ринкової сегментацією. Це шлях до стійкого сільського господарства шляхом диверсифікації технологій, культур і порід худоби, через мережу, що об'єднує всіх учасників АПК. У статті авторами були визначені перспективи і проблеми на шляху впровадження ІКТ в сільське господарство. Зокрема, інформаційно-комунікаційні технології і управління даними можуть створити новаторські способи створення прибуткового, суспільно прийнятного сільського господарства. Але на шляху нових технологій виникають і такі суттєві перешкоди, як висока вартість їх впровадження на індивідуальних фермах і недолік знань і навичок у фермерів. Особливо це стосується країн, що розвиваються. Впровадження нових технологій в сільське господарство може вплинути на скорочення кількості робочих місць в галузі. RU: Применение информационно-коммуникационных технологий - гармоничный путь выхода из замкнутых технологий, которые характеризуются сильной поляризацией и рыночной сегментацией. Это путь к устойчивому сельскому хозяйству путем диверсификации технологий, культур и пород скота через сеть, объединяющую всех участников АПК. В статье авторами были определены перспективы и проблемы на пути внедрения ИКТ в сельское хозяйство. В частности, информационно-коммуникационные технологии и управления данными могут создать новаторские способы создания прибыльного, общественно приемлемого сельского хозяйства. Но на пути новых технологий возникают и такие существенные препятствия, как высокая стоимость их внедрения на индивидуальных фермах и недостаток знаний и навыков у фермеров. Особенно это касается развивающихся стран. Внедрение новых технологий в сельское хозяйство может повлиять на сокращение количества рабочих мест в отрасли. EN: Agriculture is one of the oldest spheres of human activity, but today it cannot stay away from total digitalization. The use of information and communication technologies is a harmonious way out of closed technologies, which were characterized by strong polarization and market segmentation. This is the path to sustainable agriculture through the diversification of technologies, crops and livestock, through a network that unites all participants in agriculture. The authors emphasize that information and communication technologies allow farmers to exchange information, develop cooperation and search for partners, and even develop informal information systems that complement formal systems of government control. Such a cycle of information between farmers, between farmers and consumers would be independent of scale and not limited by state borders. Prospects and problems on the way of introduction of ICT in agriculture were identified. In particular, information and communication technologies and data management can create innovative ways to create profitable, socially acceptable agriculture that benefits the environment (soil, water, climate), biodiversity, and farmers in different countries. But this can only happen in the context of a far-sighted policy of supporting the necessary legal and market infrastructure for smart farming, dialogue between supporters and opponents of certain agricultural technologies and with tactful consideration of ethical issues. But in the way of new technologies there are such significant obstacles as the high cost of their implementation on individual farms and the lack of knowledge and skills of farmers. This is especially true in developing countries. Therefore, access to the latest technologies may remain a limited narrow circle of large industrial farms. Accordingly, the effect of modern technologies in the field of informatics and communications will be mainly developed countries and producers of major field crops, such as wheat, corn or rice. It also increases the risk of unsustainable intensification. The introduction of new technologies in agriculture can reduce the number of jobs in the industry.
Перспективы и проблемы развития информационных технологий в сельском хозяйстве
Prospects and problems of development of information technologies in agriculture
Keywords: сільське господарство; інформаційно-комунікаційні технології; впровадження; перспективи; проблеми; сельское хозяйство; информационно-коммуникационные технологии; внедрение; перспективы; проблемы; agriculture; information and communication technologies; implementation; prospects; problems